Anticancer activity of eugenol from clove (Syzygium aromaticum L.) against MCF-7 breast cancer cells: in silico and in vitro evaluation - Shofyani, Siti Hajar Permatahati; Prastiyanto, Muhammed Evy; Geleta, Daniel; Putri, Wahyu (Archive of Oncology, 2026)
Breast cancer is a major cause of cancer-related deaths among women globally. Despite notable progress in the treatment options, the pursuit of effective natural-based therapeutic alternatives continues to be essential. Syzygium aromaticum L. (cloves) is rich in eugenol, a phenolic compound known for its antimicrobial, anti-inflammatory, and anticancer effects. This study aimed to assess the anticancer activity of eugenol extracted from cloves against MCF-7 breast cancer cells using in silico molecular docking and in vitro cytotoxicity assays. The cloves collected from Natuna District and Magetan District (Indonesia) were extracted through Soxhlet extraction with n-hexane and maceration with ethanol. Gas Chromatography-Mass Spectrometry (GC-MS) analysis identified eugenol as the primary component, making up 53.6% of the Soxhlet extract. The molecular docking results indicated that eugenol has significant binding affinities for AKT (-5.1 kcal/mol) and ESR1 (-5.9 kcal/mol), two essential proteins involved in the proliferation and survival of breast cancer cells. Cytotoxicity assessments using the MTT assay revealed a dose-dependent decrease in MCF-7 cell viability, with notable inhibition occurring at concentrations between 15.625 and 2.000 ppm. These results suggest that the eugenol-rich clove extract demonstrates promising anticancer potential by exerting direct cytotoxic effects and influencing key molecular targets within the breast cancer signalling pathway.